Penggunaan Video Sebagai Strategi Pembelajaran dalam Mendukung Peningkatan Pengetahuan dan Keterampilan Klinis Mahasiswa Keperawatan - Sari, Indah Permata; Sundari, Sri (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Video is a promising, relevant, and increasingly used form of learning media that can improve the quality ofeducation. This study aims to further examine the use of video as a learning strategy in supporting the knowledgeand clinical skills of nursing students. This study uses a quasi-experiment with pretest and posttest design tocompare video methods and lecture methods in nursing students. The research sample population was 60respondents and the research data collection method used the MCQ (Multiple Choice Question) questionnairesheet for the assessment of the knowledge, while the OSCE (Objective Structured Clinical Examination) sheet forthe assessment of students' clinical skills. Based on the results of research using paired t-test, posttest t-test, andhypothesis testing using independent sample t-test that the value of t count > t table (p-value = 0,000 <0.05), so thatthe value is significant in improving both aspects of the assessment. The video method has a higher average scoreand improvement than the lecture method.